Deferasirox limits cartilage damage following haemarthrosis in haemophilic mice - Nieuwenhuizen, Laurens; Roosendaal, Goris; Mastbergen, Simon C.; Coeleveld, Katja; Biesma, Douwe H.; Lafeber, Floris P. J. G.; Schutgens, Roger E. G. (Thrombosis and Haemostasis, 2014)
Joint bleeds in haemophilia result in iron-mediated synovitis and cartilage damage. It was evaluated whether deferasirox, an iron chelator, was able to limit the development of haemophilic synovitis and cartilage damage. Haemophilic mice were randomly assigned to oral treatment with deferasirox (30 mg/kg) or its vehicle (control) (30 mg/kg). Eight weeks after start of treatment, haemarthrosis was induced. After another five weeks of treatment, blood-induced synovitis and cartilage damage were determined. Treatment with deferasirox resulted in a statistically significant (p< 0.01) decrease in plasma ferritin levels as compared to the control group (823 ng/ml ± 56 and 1220 ng/ml ±114, respectively). Signs of haemophilic synovitis, as assessed by the Valentino score [range 0 (normal) – 10 (most affected)], were not different (p=0.52) when comparing the control group with the deferasirox group. However, deferasirox treatment resulted in a statistically significant (p< 0.01) reduction in cartilage damage, as assessed by the loss in Safranin O staining [range 0 (normal) – 6 (most affected)], when comparing the deferasirox group with the control group: score 2 (65.4 % vs 4.2 %), score 3 (26.9 % vs 4.2 %), score 4 (7.7 % vs 20.8 %), score 5 (0 % vs 54.2 %), and score 6 (0 % vs 16.7 %). Treatment with deferasirox limits cartilage damage following the induction of a haemarthrosis in haemophilic mice. This study demonstrates the role of iron in blood-induced cartilage damage. Moreover, these data indicate that iron chelation may be a potential prevention option to limit the development of haemophilic arthropathy.
Keywords: Haemophilia; haemarthrosis; blood-induced arthropathy; deferasirox